Figurations in Indian Film - Sen, Meheli; Basu, Anustup; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This volume brings together a series of essays that interrogate the notion of figuration in Indian cinemas. The essays collectively argue that the figures which exhibit maximum tenacity in Indian cinema often emerge in the interface of recognizable binaries: self/other, Indian/foreign, good/bad, virtue/vice, myth/reality and urban/rural.
Keywords: Motion pictures—Production and direction; Motion pictures—History.; Motion pictures and television; Film genres; Communication; Directing; Film History; Screen Studies; Genre; Media Studies